Arginase 1 Insufficiency Precipitates Amyloid-β Deposition and Hastens Behavioral Impairment in a Mouse Model of Amyloidosis - Ma, Chao; Hunt, Jerry B.; Selenica, Maj-Linda B.; Sanneh, Awa; Sandusky-Beltran, Leslie A.; Watler, Mallory; Daas, Rana; Kovalenko, Andrii; Liang, Huimin; Placides, Devon; Cao, Chuanhai; Lin, Xiaoyang; et al. (Frontiers in Immunology, 2021)
Alzheimer’s disease (AD) includes several hallmarks comprised of amyloid-β (Aβ) deposition, tau neuropathology, inflammation, and memory impairment. Brain metabolism becomes uncoupled due to aging and other AD risk factors, which ultimately lead to impaired protein clearance and aggregation. Increasing evidence indicates a role of arginine metabolism in AD, where arginases are key enzymes in neurons and glia capable of depleting arginine and producing ornithine and polyamines. However, currently, it remains unknown if the reduction of arginase 1 (Arg1) in myeloid cell impacts amyloidosis. Herein, we produced haploinsufficiency of Arg1 by the hemizygous deletion in myeloid cells using Arg1fl/fl and LysMcreTg/+ mice crossed with APP Tg2576 mice. Our data indicated that Arg1 haploinsufficiency promoted Aβ deposition, exacerbated some behavioral impairment, and decreased components of Ragulator-Rag complex involved in mechanistic target of rapamycin complex 1 (mTORC1) signaling and autophagy. Additionally, Arg1 repression and arginine supplementation both impaired microglial phagocytosis in vitro. These data suggest that proper function of Arg1 and arginine metabolism in myeloid cells remains essential to restrict amyloidosis.